2010
DOI: 10.1152/physiolgenomics.00055.2010
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the regulatory control of vertebrate striated muscle: the roles of troponin I and myosin binding protein-C

Abstract: Troponin I (TnI) and myosin binding protein-C (MyBP-C) are key regulatory proteins of contractile function in vertebrate muscle. TnI modulates the Ca(2+) activation signal, while MyBP-C regulates cross-bridge cycling kinetics. In vertebrates, each protein is distributed as tissue-specific paralogs in fast skeletal (fs), slow skeletal (ss), and cardiac (c) muscles. The purpose of this study is to characterize how TnI and MyBP-C have changed during the evolution of vertebrate striated muscle and how tissue-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 71 publications
(98 reference statements)
5
66
2
Order By: Relevance
“…A similar scheme for the evolution of other contractile proteins has also been suggested by Oota and Saitou (Ota and Saitou, 1999). We have also suggested that the similarity between cTnI from fish species and ssTnI indicates that there has been little change in the sequence of fish cTnI since this group diverged from the vertebrate lineage (Shaffer and Gillis, 2010). The results of the current study demonstrating that trout cTnI increases the Ca 2+ affinity of the cTn complex, as does ssTnI, support this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A similar scheme for the evolution of other contractile proteins has also been suggested by Oota and Saitou (Ota and Saitou, 1999). We have also suggested that the similarity between cTnI from fish species and ssTnI indicates that there has been little change in the sequence of fish cTnI since this group diverged from the vertebrate lineage (Shaffer and Gillis, 2010). The results of the current study demonstrating that trout cTnI increases the Ca 2+ affinity of the cTn complex, as does ssTnI, support this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…These results provide evidence that cTnI from fish can be viewed as ancestral or primitive forms of the paralogous protein in mammalian cardiac tissue. This hypothesis is supported by previous phylogenetic studies of vertebrate TnI (Shaffer and Gillis, 2010). The sensitizing effect of trout cTnI on the mammalian cTn complex suggests that this protein is involved in the comparatively high Ca 2+ sensitivity of the trout heart and therefore helps enable cardiac function at low temperatures.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations